Ocena przydatności wybranych metod badawczych w diagnostyce jaskry u pacjentki z druzami tarczy nerwu wzrokowego. Opis przypadku - Grabska-Liberek, Iwona; Polaczek-Krupa, Barbara; Jankowska-Lech, Irmina (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: The aim of the study is an evaluation of applicability of selected test in glaucoma diagnosis in a patient with optic disc drusen. Material and methods: The authors describe a case of a patient examined for glaucoma because of an increased intraocular pressure and deterioration of vision. The optic disc drusen were found in the patient by ophthalmoscopy and confirmed by ultrasonography. The patient was examined by the scanning laser ophthalmoscopy HRT, scanning laser polarymetry GDX, retina thickness analysis RTA and determination of the visual field. Results: Results of diagnostic studies were presented in the paper. The scanning laser ophthalmoscopy did not evidence any presence of glaucomatous cup in the optic nerve head. The scanning laser polarymetry showed extensive losses in nerve fiber layer of retina and the retinal thickness analysis showed a reduction of the retina thickness in the posterior pole. Study of the vision field evidenced the relative and absolute scotomas. Conclusions: The results show a necessity for careful evaluation of the glaucoma examination results in patients with drusen in the optic nerve head, because of a high similarity of abnormalities produced by both diseases.